Biological aspects of Harmonia axyridis fed on two prey species and intraguild predation with Eriopis connexa - Santos, Natália Ribeiro Pereira dos; Santos-Cividanes, Terezinha Monteiro dos; Cividanes, Francisco Jorge; Anjos, Anna Carolina Ribeiro dos; Oliveira, Leliz Vaz Leite de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine the biological aspects of Harmonia axyridis, fed on two prey species, and the occurrence of intraguild predation with Eriopis connexa. Larvae of H. axyridis were fed daily with Anagasta kuehniella eggs or Schizaphis graminum aphid. Adults of H. axyridis were separated in ten couples which received the same food type of the larval stage. For the estimation of predation, a fourth instar larva of each species was maintained in the presence or absence of shelter and eggs of A. kuehniella. The larval stage lasted 10.2 days, when H. axyridis fed on A. kuehniella eggs, and 8.9 days when reared with S. graminum. The survival of predator during immature stages ranged from 70 to 100%. H. axyridis had an oviposition period of 47.3 and 51.7 days, laying a total of 887.6 and 822.5 eggs, when fed on A. kuehniella and S. graminum, respectively. Females had longevity of 74.1 and 76.2 days, and males of 67.3 and 70.3 days, fed on A. kuehniella and S. graminum, respectively. H. axyridis acted as an intraguild predator and was the dominant species in the competition with E. connexa.
Keywords: Coccinellidae; Coleoptera; biological control